The Mechanism of Neutralization of Corruption Threat in Commercial Sector - Viktor Petrovich Kirilenko; Roman Vladimirovich Dronov; Alexey Mikhailovich Shunaev (Управленческое консультирование)
Corruption as a kind of corporate fraud poses a significant threat to the normal activity in commercial sector of economy. The article describes the threat of fraud and abuse of official position in the commercial sector of economy. There is analysis the statistics of detected cases of fraud and effectiveness of the measures used to neutralize the threat of corruption.